THE INFLUENCE OF DIGITAL TECHNOLOGIES ON TEACHING METHODOLOGIES: A SYSTEMATIC LITERATURE REVIEW - Johni Eka Putra; Nuraini Nuraini (Adisam Publisher, 2025)
This research aims to examine the influence of digital technologies on teaching methodologies through a systematic literature review. With the rapid development of digital technologies in the last decade, understanding their impact on teaching practices has become increasingly important. The results show that digital technologies have significantly changed teaching methodologies, encouraging a more interactive, personalised and student-centred approach. The use of Learning Management Systems (LMS), mobile learning applications and online collaboration tools has increased the flexibility and accessibility of learning. However, research also revealed challenges such as the digital divide, the need for teacher training, and the importance of proper learning design. Thus, this review concludes that while digital technologies offer great potential to improve teaching, their effectiveness depends on careful implementation and ongoing support for educators and learners. Implications for future research and educational practice are also discussed.